Disseminated Primary Herpes Simplex Virus Type 2 Infection in a 22-Year-Old male. (16th June 2015) - Erdmann, Nathan; Hewitt, Benjamin A.; Atkinson, Thomas Prescott; Van Wagoner, Nicholas
Abstract: We present a case of primary disseminated herpes simplex virus type 2 (HSV-2) cutaneous disease in a 22-year-old male. We discuss the immune response to HSV-2 infection as well as the extragenital manifestations of HSV-2 observed in immune-competent and immune-suppressed persons.